Research on time–frequency characteristics of contact force based on wavelet transform - Fang He; Jian Zhang (IET Electrical Systems in Transportation)
Abstract When a train runs at high speed, affected by the structural characteristics of the catenary, the contact force changes periodically with span and dropper spacing. However, as the running speed of the train increases, the periodic signal of the contact force changes owing to the fluctuation of the catenary and the vibration of the pantograph, which directly affects the stable contact between the pantograph and catenary. Therefore, based on the simulation research method, this study uses the time–frequency transformation method to investigate the influence of changes in the catenary structure on the periodic signal of the contact force. First, the structural design of the catenary structure of the existing railway line is carried out by changing the length of the stitch wires and the dropper spacing, and the stiffness and stiffness curvature variation when the arrangement of the stitch wires and dropper varies are analysed. Then, the relationship between the stiffness, stiffness curvature variation, and contact force variation is analysed. Finally, the wavelet transform method is used to transform the contact force, and variations in the key amplitude component of the contact force are analysed when the structural parameters are changed, and the relationship between the period and the key amplitude component is obtained. By analysing the time–frequency characteristics of the contact force, technical support for improving the speed of the train can be provided.